Adjustable Quadrature Shadow Sinusoidal Oscillator - Seangrawee Buakaew; Narin Atiwongsangthong (My University, 2022)
This article presents a shadow oscillator with quadrature-phase outputs. The proposed circuit employs the voltage differential transconductance amplifier (VDTA) and two grounded passive elements. The frequency of the oscillation, as well as the condition of oscillation, are accomplished through the tunning of the gains of the external amplifiers. Therefore, frequency adjustability can be performed without the effect on the biquad cell which is the main feature of the shadow oscillators. The results from the PSpice simulations employing the CMOS circuit level are included to verify the proposed quadrature shadow oscillator configurations.
Keywords: Analog and Mixed-Signal Circuit Design; Radio Frequency Integrated Circuit Design; Advancements in PLL and VCO Technologies